2003
DOI: 10.1111/j.1524-6175.2002.2041.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Goal Blood Pressure in Patients With Type 2 Diabetes: Conventional Versus Fixed‐Dose Combination Approaches

Abstract: Data from the Third National Health and Nutrition Examination Survey (NHANES III) demonstrate that only 11% of people with diabetes who are treated for high blood pressure achieve the blood pressure goal of <130/85 mm Hg recommended in the sixth report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC VI). The current study tests the hypothesis that initial therapy with a fixed-dose combination will achieve the recommended blood pressure goal in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 37 publications
2
57
1
2
Order By: Relevance
“…We identified a substantial effect of A therapy (B25/11 mm Hg) and an additional BP lowering (B5/3 mm Hg) attributable to the combination of amlodipine and benazapril. The observation that BP control rates in this study are lower than those reported in other studies, 6,7 owes, at least in part, to the very high baseline SBP and DBP measurements that were present (about 175/100 mm Hg); thus, a mean decrease in SBP of 435 mm Hg and DBP of 420 mm Hg would have been necessary to achieve BP control in the majority of subjects. More important is the strict guideline-based definition of BP control that was used (o140/90 in general or o130/80 mm Hg in subjects with diabetes or CKD).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…We identified a substantial effect of A therapy (B25/11 mm Hg) and an additional BP lowering (B5/3 mm Hg) attributable to the combination of amlodipine and benazapril. The observation that BP control rates in this study are lower than those reported in other studies, 6,7 owes, at least in part, to the very high baseline SBP and DBP measurements that were present (about 175/100 mm Hg); thus, a mean decrease in SBP of 435 mm Hg and DBP of 420 mm Hg would have been necessary to achieve BP control in the majority of subjects. More important is the strict guideline-based definition of BP control that was used (o140/90 in general or o130/80 mm Hg in subjects with diabetes or CKD).…”
Section: Discussioncontrasting
confidence: 68%
“…More important is the strict guideline-based definition of BP control that was used (o140/90 in general or o130/80 mm Hg in subjects with diabetes or CKD). We have found only two studies with limited similarity: SOLACE by Jamerson et al 6 and SHIELD by Bakris et al, 7 in which BP control rates were 61 and 63%, respectively. Each of these studies was of 12 weeks in duration, whereas our study was much shorter (6 weeks).…”
Section: Discussionmentioning
confidence: 93%
“…The improvement in BP following the correction of Atlas misalignment is similar to that seen by giving two different antihypertensive agents simultaneously. 11,12 Moreover, this reduction in BP persisted at 8 weeks and was not associated with pain or pain relief or any other symptom that could be associated with a rise in BP.…”
Section: Discussionmentioning
confidence: 87%
“…Combining classes of agents with complementary mechanisms of action, such as CCBs and RAS blockers, provides greater BP-lowering efficacy than monotherapy, [68][69][70][71][72][73][74][75] with a comparable and potentially improved adverse-event profile. 76 However, few trials have been designed to test the effect of specific antihypertensive combinations on cardiovascular or renal end points.…”
Section: Dual Calcium Channel/ras Blockadementioning
confidence: 99%